KAJIAN TOPONIMI PERKITARAN ISTANA ALWATZIKHOEBILLAH KABUPATEN SAMBAS - Safitri, Ade; Syahrani, Agus; Jupitasari, Mellisa (Universitas Tanjungpura, 2023)
This study aims to describe the calasification of toponymy studies, the meaning of toponymy studiesz and produce a desriptive text structure of the Alwatzikhoebillah Palace, a supplement for learning Indonesian for class VII descriptive text material based on the study of toponymy around the Alwatzikhoebillah Palace. The method used in this study is a qualitative method. The source of the data in this study is the speech of the informant who understands the study of toponymy or the naming of place names at the Alwatzikhoebillah Palace, Sambas Regency. Data collection technique are observation, interview, and note taking technique. Based on the overall data that has been analyzed, the are six naming classifications based on their referents, namely 4 categories based on plants, 2 categories based on ethnicity, 8 categories based on people's name, 9 categories based on stories, 1 category based on historical object, and 1 category based on buildings. The total number of data is 25. The meaning of the toponymy study consist of four types of meaning, namely lexical meaning, grammatical meaning, referential meaning, and associative meaning, implemented for desriptive text teaching materials in Indonesian language subject in the 2013 curriculum for class Vll odd semesters.